Hubungan Penerapan Plant-Based Diet Dalam Penurunan Risiko Hipertensi: Review - Astuti, Widya; Anggiruling, Dwikani Oklita (Jurnal Gizi dan Kuliner, 2022)
The prevalence of non-communicable diseases (NCD) increases continuously every year and this is the biggest factor causing death. Based on WHO data in 2020, 73% of deaths in Indonesia were caused by NCD. Hypertension belongs to NCD and the main cause of death in the world. The consumption pattern of the plant-based diet contains a lot of fiber, magnesium, folic acid, Fe3+, vitamins C and E, n-6 polyunsaturated fatty acids (PUFA), antioxidants, carotenoids, flavonoids, and other phytochemicals so can prevent hypertension. The purpose of this article was to find out the benefits of implementing a plant-based diet in reducing the risk of hypertension, based on the results of research that has been performed. The method used in this article is randomized control trials (RCTs) on articles published with sources from Google Schoolar, PubMed, and Elsevier. The results of the review showed that there was a significant relationship in the application of the plant-based diet to the reduction of blood pressure and the risk of hypertension in various age groups. However, the application of a plant-based diet can cause micronutrient deficiencies. Therefore, the application of a plant-based diet was good for preventing the risk of hypertension and accompanied by the selection of various types of food. Keywords : hipertensi, plant-based diet, vegetarian diet